2020
DOI: 10.3390/app10030936
|View full text |Cite
|
Sign up to set email alerts
|

A Heterogeneous Ensemble Learning Framework for Spam Detection in Social Networks with Imbalanced Data

Abstract: The popularity of social networks provides people with many conveniences, but their rapid growth has also attracted many attackers. In recent years, the malicious behavior of social network spammers has seriously threatened the information security of ordinary users. To reduce this threat, many researchers have mined the behavior characteristics of spammers and have obtained good results by applying machine learning algorithms to identify spammers in social networks. However, most of these studies overlook cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(32 citation statements)
references
References 42 publications
0
32
0
Order By: Relevance
“…To deal with the problem of class imbalance of spam detection in social networks, Zhao et al [68] proposed a heterogeneous stacking-based ensemble learning framework, which consists of two main modules: a base module and a combined module. In the base module, they trained six separate base classifiers to generate meta-data with new features, which are fed to the combined module.…”
Section: Shallow Learning-based Detection Methodsmentioning
confidence: 99%
“…To deal with the problem of class imbalance of spam detection in social networks, Zhao et al [68] proposed a heterogeneous stacking-based ensemble learning framework, which consists of two main modules: a base module and a combined module. In the base module, they trained six separate base classifiers to generate meta-data with new features, which are fed to the combined module.…”
Section: Shallow Learning-based Detection Methodsmentioning
confidence: 99%
“…Table 5 and Fig. 14 computes a detailed comparative results analysis of the CIDD-ADODNN model on the test Spam dataset [23][24][25]. The resultant scores reported that HELF and KNN models have depicted inferior performance by obtaining lower accuracy values of 0.750 and 0.818, respectively.…”
Section: Performance Validationmentioning
confidence: 99%
“…To prevent misclassifications, which can be fatal to the filter, we use a cost-based machine learning technique. This method sets a different cost for errors that occur in the case of misclassification and attempts to minimize the sum of costs [43,44]. The asymmetric classification cost matrix is presented in Table II.…”
Section: Figure 1 Workflow Of the Proposed Frameworkmentioning
confidence: 99%
“…If is a resample that has examples, is a model generated by applying the machine learning algorithm to . Here, the risk that results when belongs to class can be defined as follows [44]:…”
Section: Figure 1 Workflow Of the Proposed Frameworkmentioning
confidence: 99%